1979
DOI: 10.1002/jlcr.2580160310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, chromatography and tissue distribution of methyl‐11c‐morphine and methyl‐11C‐heroin

Abstract: SUMMARY"C-Morphine was prepared by methylation of normorphine with CH31. Acetylation of this compound yields heroin. The radiochemical yield is 9% for morphine and 4 % for heroin at a specific activity of 1.63 mCi/pmole. Synthesis time including purification by hplc is 18 min for "C-morphine and 36 min for llC-heroin, respectively. The tissue distribution of both these compounds was determined in rats at different times after an i.v. injection.The main accumulation of activity is in the small intestine, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although the synthesis of carbon-11 labeled morphine was originally reported in the 1970’s, either by reductive alkylation using [ 11 C]formaldehyde combined with sodium borohydride (Allen and Beaumier 1979) or by N -methylation using [ 11 C]CH 3 I with a base in ethanol (Kloster et al, 1979) or dimethyl formate (DMF) (Långström et al, 1982), the reaction conditions and processes have never been optimized. In addition, no automated radiosynthetic procedure of producing the [ 11 C]morphine for human studies was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Although the synthesis of carbon-11 labeled morphine was originally reported in the 1970’s, either by reductive alkylation using [ 11 C]formaldehyde combined with sodium borohydride (Allen and Beaumier 1979) or by N -methylation using [ 11 C]CH 3 I with a base in ethanol (Kloster et al, 1979) or dimethyl formate (DMF) (Långström et al, 1982), the reaction conditions and processes have never been optimized. In addition, no automated radiosynthetic procedure of producing the [ 11 C]morphine for human studies was reported.…”
Section: Resultsmentioning
confidence: 99%
“…However, a high dissociation rate from the receptor was evident. A low radioactive uptake and poor selectivity have previously been shown for other opioid receptor agonists in the brain (Hartvig et al 1984;Kloster et al 1979). Pethidine is a selective p-opioid receptor agonist and the receptor affinity has been shown to be less than one tenth that of morphine (Yaksh 1986), which has an afinity in the low nmol range (Pasternak 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Although not mentioning the terms opiate or receptor in the publication, the synthesis and tissue distribution of two carbon-11-labeled opiate radioligands (morphine and heroin) prepared from [ 11 C]iodomethane were the focus of a 1979 publication. 9 The authors reported observing little activity in the brain for either radioligand. The earliest publication that did describe a synthesis of a PET radiotracer for studying opiate receptors in brain in vivo came from the laboratory of Comar in 1981 where Mazière et al described the synthesis of [ 11 C]etorphine (Figure 1) from [ 11 C]formaldehyde at moderate specific activity and good radiochemical yield.…”
Section: Early Effortsmentioning
confidence: 98%
“…Although not mentioning the terms opiate or receptor in the publication, the synthesis and tissue distribution of two carbon‐11‐labeled opiate radioligands (morphine and heroin) prepared from [ 11 C]iodomethane were the focus of a 1979 publication . The authors reported observing little activity in the brain for either radioligand.…”
Section: Early Effortsmentioning
confidence: 99%